PENGARUH SENAM ERGONOMIK TERHADAP TINGKAT NYERI PENDERITA OSTEOARTRITIS PADA LANSIA DI RUMAH ASUH ANAK DAN LANSIA WREDHA GRIYA ASIH LAWANG - Kurniawan, Andi Surya; Rochmawati, Erna (Journal Nursing Care and Biomolecular, 2018)
Osteoarthritis that occurs in the elderly is a chronic degenerative disease, complaints that often occur in the form of pain. Interventions can be done to deal with pain by doing ergonomic exercises. This type of research uses quantitative with quasi-experimental, the type of design is pre-posttest with control group design. The number of samples consisted of 16 elderly intervention groups and 16 elderly control groups. The intervention group was given ergonomic exercise, in the control group given elderly gymnastics. The results showed that there were significant differences in the two groups. Based on paired t-test and independent t-test in the intervention group there was a decrease in pain level of 2.07 while in the control group there was a decrease in pain level of 1.07 statistically the two influential groups were significantly evidenced by the value p> 0.05.. The conclusion of this study is that ergonomic exercise affects the pain of patients with osteoarthritis in the elderly